DAKWAH KULTURAL DI TANOH GAYO - Ali Mustafa (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This research reviewed the existence of cultural da'wah in the spread of Islam in Gayo land of middle Aceh within the historical perspective. This research found that the model and apporach of da'wah cultural in gayonesse people in middle Aceh are not in line with islamic value. In this approach, the terms, deeds and cultural equipments used are genuinely parts of Gayo culture. Yet, islamic values were inserted in this approach. This approach made Islam easy to be eccepted by gayonesse who are previously animism. Moreover, the support of sarak opat as opinion leader made the spreading of islam easier and firm in every daily aspects of gayo people. As the result, the acculturation between culture and religion occured which makes the gayo culture identycal with the values of islam.